Industrial training report: National Library of Malaysia / Wahida Ashikin Mamat - Mamat, Wahida Ashikin (Universiti Teknologi MARA, Negeri Sembilan, 2018)
These paper were about the reports that were written to fulfill the requirement of subject Industrial Training (IMC 690) after end of the practical training from 2th February 2018 until 29 Jun 2016. Bachelor degree student in Faculty of Information Management precisely are require to undergo an industrial training for twenty weeks as a part of our requirement to complete the 3 and half year in my case for course of Bachelor of Science (Hons.) Library and Information Management. During this five-month period of industrial training, students are supervised and monitored their training by two nominated supervisors which are one from the faculty and one from the organization of the industrial training. The industrial training subject provides preprofessional work experience with specific assignment and responsibilities. The report was about all the activities and task assigned during the industrial training National Library of Malaysia. It gives the experience, skills and new knowledge in information management field that will improve the career opportunity of the trainee in the future. This paper also contains the information about the special project done by the trainee during the industrial training at National Library of Malaysia.